2010
DOI: 10.1253/circj.cj-09-0791
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Assessment and Clinical Strategy of Stable Coronary Artery Disease by Magnetic Resonance Imaging, Multislice Computed Tomography and Myocardial Perfusion SPECT

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp ecent development in non-invasive imaging modalities, such as multislice computed tomography (MSCT) and magnetic resonance imaging (MRI), have gained great attention in the field of diagnostic cardiology, especially in the diagnosis of coronary artery disease (CAD). These imaging modalities have clinical advantages over other imaging techniques including stress echocardiography and stress single-photon emission co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…23 It has also been noted that induced ischemia was one of the major determinants for patient management. 3, 25 In other words, low-risk patients were considered to be suitable for medical treatment, and high-risk patients required more aggressive treatment including coronary revascularization. Hachamovitch et al found that patients with >10% ischemia could expect more beneficial effects from coronary revascularization.…”
Section: Role Of Risk Evaluationmentioning
confidence: 99%
“…23 It has also been noted that induced ischemia was one of the major determinants for patient management. 3, 25 In other words, low-risk patients were considered to be suitable for medical treatment, and high-risk patients required more aggressive treatment including coronary revascularization. Hachamovitch et al found that patients with >10% ischemia could expect more beneficial effects from coronary revascularization.…”
Section: Role Of Risk Evaluationmentioning
confidence: 99%
“…We have previously documented that myocardial perfusion SPECT could be used to predict future cardiac events (nonfatal AMI and cardiac death (CD)) in a Japanese population. [7][8][9] In the present study we investigated whether ECG-gated SPECT can still give prognostic information for patients with DM in terms of those major cardiac events. Recently, a Japanese assessment of cardiac events and survival by quantitative gated SPECT (J-ACCESS 2) in patients with asymptomatic DM documented the short-term cardiac event rates (ie, in 1 year).…”
mentioning
confidence: 99%
“…5, 19 In a Japanese population using MPI, a study demonstrated that advanced age, SSS, and summed difference score were independent predictors of cardiac death. 20, 21 The equation for predicting cardiac events was based on multi-variate analysis of J-ACCESS investigation. Based on a 3-year follow-up study of 4,629 patients, major cardiac events including cardiac death, non-fatal myocardial infarction, and severe heart failure requiring hospitalization could be estimated.…”
Section: Discussionmentioning
confidence: 99%